PENGEMBANGAN APLIKASI PEMESANAN ONLINE DENGAN QR CODE MENGGUNAKAN FRAMEWORK LARAVEL BERBASIS COLLABORATIVE FILTERING DI GERDU KAFFE PAITON PROBOLINGGO - Yaqin, Moh Ainol; Syafiih, M (Journal of Advanced Research in Informatics, 2024)
"Gerdu Kaffe" still relies on manual methods for ordering and data management, despite the fact that cafes serve as social interaction spaces. This system encounters several issues, such as menu lists getting damaged or lost, difficulties in menu updates, long queues, and errors in manual ordering during peak hours. This research aims to develop a Menu Ordering Application with QR Code using the Laravel framework and employs Collaborative Filtering techniques. This application allows customers to order food and beverages through a smartphone using a QR Code Reader. Collaborative Filtering is used to analyze user preferences and behavior to discover relevant patterns. The research method used is qualitative, involving interviews and observations. Testing using blackbox testing methods resulted in the highest percentage of 86%, indicating that this web-based menu ordering system is effective in assisting the management process at Gerdu Kaffe Paiton.